EFFECT OF FDM PROCESS PARAMETERS ON TENSILE STRENGTH BASED ON FLUID THERMAL ANALYSIS (MT) - CHENG GuoFeng; DING ZiShan (Jixie qiangdu)
Fused Deposition Modeling（FDM） has the advantages of fast forming speed and simple operation. Printing speed, printing layer thickness and printing temperature affect the equivalent stress of the workpieces, and then affect its mechanical properties. It is different from direct setting printing temperature as the initial temperature in the birth and death unit simulation. Through experiment and fluid simulation, the temperature of the single fuse when it contacts the plate is got, as the initial temperature of the multilayer superposition simulation. We calculate and fit out the function of heat transfer coefficient, considering printing parameters. With the FDM Multi Layer Stacking simulation, the stress of the workpieces under different parameters is got. Then correlated and compared with the tensile strength obtained by the tensile test under the same parameters. From the point of the stress, we analyzed the influence of the printing parameters on the tensile strength. The supplementary experiment is designed, and find the tensile strength of ploylactic acid（PLA） workpieces reach the maximum when the printing layer thickness is as far as small, the printing speed and the printing temperature are appropriate.